Vortex-Induced Injectable Silk Fibroin Hydrogels - Yucel, Tuna (The Biophysical Society, 2009)
A novel, to our knowledge, technique was developed to control the rate of β-sheet formation and resulting hydrogelation kinetics of aqueous, native silk solutions. Circular dichroism spectroscopy indicated that vortexing aqueous solutions of silkworm silk lead to a transition from an overall protein structure that is initially rich in random coil to one that is rich in β-sheet content. Dynamic oscillatory rheology experiments collected under the same assembly conditions as the circular dichroism experiments indicated that the increase in β-sheet content due to intramolecular conformational changes and intermolecular self-assembly of the silk fibroin was directly correlated with the subsequent changes in viscoelastic properties due to hydrogelation. Vortexing low-viscosity silk solutions lead to orders-of-magnitude increase in the complex shear modulus, G(∗), and formation of rigid hydrogels (G(∗) ≈ 70 kPa for 5.2 wt % protein concentration). Vortex-induced, β-sheet-rich silk hydrogels consisted of permanent, physical, intermolecular crosslinks. The hydrogelation kinetics could be controlled easily (from minutes to hours) by changing the vortex time, assembly temperature and/or protein concentration, providing a useful timeframe for cell encapsulation. The stiffness of preformed hydrogels recovered quickly, immediately after injection through a needle, enabling the potential use of these systems for injectable cell delivery scaffolds.